2012
DOI: 10.1016/j.vetimm.2012.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Induction and characterization of endotoxin tolerance in equine peripheral blood mononuclear cells in vitro

Abstract: Endotoxemia is responsible for severe illness in horses. Individuals can become unresponsive to the endotoxin molecule after an initial exposure; this phenomenon has been called developing a state of 'endotoxin tolerance' (ET). ET has been induced in horses in vivo; however, cytokine expression associated with ET has not been investigated. The purpose of this study was to develop and validate a method for inducing ET in equine peripheral blood mononuclear cells (PBMCs) in vitro, and to describe the cytokine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 137 publications
(252 reference statements)
0
2
1
Order By: Relevance
“…PCT levels in horses in this study were generally lower than levels reported in humans with SIRS . This dissimilarity might be related to the different species studied, less severe inflammation in the studied horses, or possibly endotoxin tolerance . Moreover, Yilmaz and colleagues (2008) evaluated the changes in PCT concentrations in dogs after administration of endotoxin, which resulted lower than our results.…”
Section: Discussioncontrasting
confidence: 83%
“…PCT levels in horses in this study were generally lower than levels reported in humans with SIRS . This dissimilarity might be related to the different species studied, less severe inflammation in the studied horses, or possibly endotoxin tolerance . Moreover, Yilmaz and colleagues (2008) evaluated the changes in PCT concentrations in dogs after administration of endotoxin, which resulted lower than our results.…”
Section: Discussioncontrasting
confidence: 83%
“…In this solution, the measured endotoxin concentration was the highest (approximately 10–19 ng/ml) and we cannot exclude that endotoxin tolerance was induced during the PBMC pre-incubation period, suppressing the response after the actual challenge [26]. On the other hand, the 1% solution of GOS/FOS/AOS (approximately 5–10 ng/ml endotoxin) already caused a significant reduction of the LPS response in comparison with the 0.5% GOS/FOS/AOS solution, whilst the 2% GOS/FOS solution (approximately 6–11 ng/ml endotoxin) induced a significant increase of the LPS response compared with the 1% GOS/FOS solution.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies of ET development in gene-deficient mice analyzed the participation of intracellular molecules in this process and established the roles of SHIP-1, A20 and IRAK-M. This pseudokinase could be considered a “master regulator” of ET because it is consistently induced into ET [8], [9] and is implicated in human pathologies in which ET is manifest, such as sepsis [10], cancer [11], ACS [3] and asthma [12]. In a human in vitro ET model, rapid IRAK-M up-regulation was described and is expressed in freshly isolated sepsis monocytes [10].…”
Section: Introductionmentioning
confidence: 99%